2015
DOI: 10.2298/fupct1503191b
|View full text |Cite
|
Sign up to set email alerts
|

Lead, mercury and arsenic content in spices: Black, white and green pepper, black cumin and ginger

Abstract: In order to evaluate the safety of selected commercial spices brands, concentration of lead, mercury and arsenic, as well as moisture and mineral contents were analyzed in samples of dried black and white pepper powders, black, white and green peppercorns, black cumin seeds and ginger powder. Lead (Pb), mercury (Hg) and arsenic (As) concentrations in spice samples purchased from local markets in Belgrade were determined, after a microwave digestion of the samples, by atomic absorption spectrometry (AAS), using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 29 publications
3
5
1
Order By: Relevance
“…The presented results correspond also with analyses of herbal and spice samples conducted in other European countries, e.g., in Serbia [ 54 ], in which the concentration of lead in samples of black pepper varied within the range from 0.280 mg/kg to 0.42 mg/kg. A monitoring study concerning the level of heavy metals in products in Austria [ 31 ] demonstrated that the level of lead in herbs and spices varied within the range from 0.2 mg/kg in samples of the fruit of caraway to 1.9 mg/kg in leaves of lovage.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The presented results correspond also with analyses of herbal and spice samples conducted in other European countries, e.g., in Serbia [ 54 ], in which the concentration of lead in samples of black pepper varied within the range from 0.280 mg/kg to 0.42 mg/kg. A monitoring study concerning the level of heavy metals in products in Austria [ 31 ] demonstrated that the level of lead in herbs and spices varied within the range from 0.2 mg/kg in samples of the fruit of caraway to 1.9 mg/kg in leaves of lovage.…”
Section: Resultssupporting
confidence: 86%
“…The results obtained in the presented study, concerning the level of contamination with arsenic, find support in a Malaysian study on herbs and spices commonly consumed in that country [ 40 ], in which the levels of the analysed metal varied in the range from 0.24 mg/kg in samples of bear’s garlic to 2.54 mg/kg in Philippine flower wax. Similar results of arsenic contamination were presented in a study involving the analysis of various samples of black pepper available on the Serbian market, in which arsenic was assayed in the range from 0.22 mg/kg in samples of green pepper to 0.51 mg/kg in samples of black pepper [ 54 ]. Higher levels of contamination of herbal raw materials were reported in studies conducted in Turkey [ 34 ] and Iran [ 36 ], in which the concentration of arsenic varied from 0.20 mg/kg in samples of dog rose to 19.4 mg/kg in samples of aniseed.…”
Section: Resultssupporting
confidence: 70%
“…The investigation of the toxic elements was carried out by different researchers for different cultivar samples. As (0.36, 0.33–0.51 mg/kg), Cr (5.27, 11.19 mg/kg), Pb (0.30−0.34, 0.88 0.73–0.82, 0.17–0.82, 1.1) and Cd (0.79, 0.15–0.32¸0.01–0.07, 1.16 mg/kg) were reported to have higher values than our current study (Abou‐Arab & Abou‐Donia, ; Blagojević et al, ; Krejpcio, Krol, & Sionkowski, ; Ozcan & Akbulut, ; Sherif et al, ; Ziyaina et al, ). Moreover, Cr (0.03, 0.3 mg/kg) content reported to have low amount (Seddigi et al, ; Sherif et al, ).…”
Section: Resultscontrasting
confidence: 74%
“…In fact, plants can also contain Hg due to the bioaccumulation of Hg from soil, water and atmosphere [57]. In recent years, there has been a growing interest in monitoring heavy metal contamination of spices [57][58][59]. These can contain toxic elements in a wide range of concentrations, and their content can vary according to the location and the type of soil for cultivation, fertilizers, herbicides and water resources used for irrigation, climate and environmental pollution levels [58].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been a growing interest in monitoring heavy metal contamination of spices [57][58][59]. These can contain toxic elements in a wide range of concentrations, and their content can vary according to the location and the type of soil for cultivation, fertilizers, herbicides and water resources used for irrigation, climate and environmental pollution levels [58]. The levels of toxic elements (like As, Cd, Hg and Pb) in pepper, ginger and black cumin, reported in previous studies [58], exceed in many cases the maximum limits allowed regulated by different legislations [60,61] and recommendations by WHO [62,63].…”
Section: Discussionmentioning
confidence: 99%